ChemInform Abstract: The First General Route for Efficient Synthesis of 18O Labelled Alcohols Using the HOF·CH3CN Complex. Issue 52 (24th December 2013) - Gatenyo, Julia; Vints, Inna; Rozen, Shlomo
Abstract A novel method for converting boronic acids (I) to alcohols (II) is developed using the acetonitrile complex of hypofluorous acid.